Change management : a guide to effective implementation. - McCalman, James; Paton, Rob; Siebert, Sabina (SAGE, 2016)
The fourth edition of this highly successful textbook for change management uses current examples and a more strategic focus to guide students through the issues and processes associated with managing change.